Coherent potential approximation for disordered narrow-gap semiconductor superlattices - Martínez, D.; Ruano, P. L. Alcázar; Baba, Y.; Arroyo-Gascón, O.; Domínguez-Adame, F. (Frontiers in Physics, 2025)
We introduce a solvable two-band model to study electron energy levels in disordered narrow-gap semiconductor superlattices within the k⋅p approach. The interaction of electrons with the impurities is accounted for by a separable pseudo-potential method that allows us to obtain closed expressions for the configurationally averaged Green’s function using the coherent potential approximation. This approximation is regarded as the best single-site scattering theory to calculate the average spectral properties of disordered systems. As a working example, we focus on superlattices based on IV-VI compound semiconductors and present a thorough study of the configurationally averaged density of states. Our results are compared with the predictions of a single-band model and we conclude that the latter underestimates the density of states close to the band edge.